World Bank's treatment of employment and labour market issues - Adams, Avril Van... et al (World Bank WashingtonUS, 1992)
An examination of Bank country economic and sector reports from 1985-90 reveals that wages and unemployment are the issues most often and most thoroughly treated. However while the Bank has given attention to labour market issues in the analysis of country economic and education sector reports, these issues have not been accorded priority in the policy dialogue with governments.